Provisional vs. two-stent technique for unprotected left main coronary artery disease after ten years follow up: A propensity matched analysis. (15th May 2016) - D'Ascenzo, Fabrizio; Iannaccone, Mario; Giordana, Francesca; Chieffo, Alaide; Connor, Stephen O.; Napp, L. Christian; Chandran, SujaySubash; de la Torre Hernández, José María; Chen, Shao-Liang; Varbella, Ferdinando; Omedè, Pierluigi; Taha, Salma; et al.
Abstract: Aims: There is uncertainty on which stenting approach confers the best long-term outlook for unprotected left main (ULM) bifurcation disease. Methods and results: This is a non-randomized, retrospective study including all consecutive patients with 50% stenosis of the left main involving at least 1 of the arteries stemming from the left main treated with drug-eluting stents (DES) in 9 European centers between 2002 and 2004. Patients were divided into two groups: those treated with provisional stentings vs. those treated with two stent strategy. The outcomes of interest were 10-year rates of target lesion revascularization (TLR), major adverse cardiac events (MACE), and their components (cardiovascular death, myocardial infarction [MI], or repeat revascularization), along with stent thrombosis (ST). A total of 285 patients were included, 178 (62.5%) in the provisional stenting group and 87 (37.5%) in the two stent group. After 10 years, no differences in TLR were found at unadjusted analysis (19% vs 25%, p > 0.05) nor after propensity score matching (25% vs 28%, p > 0.05). Similar rates of MACE (60% vs 66%, p > 0.05), death (34% vs 43%, p > 0.05), MI (9% vs 14%, p > 0.05) and ST were also disclosed at propensity-based analysis. Conclusion: Even after 10 year follow-up, patients treated with provisional stenting on left main showed comparable rates of target lesion revascularization compared to two stent strategy.